Pengembangan Media Pembelajaran Berbasis Android Pada Materi Alat Optik Untuk Peserta Didik SMA - Dwi Riani Mandayati; Popi Purwanti; Dasmo Dasmo (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The low achievement of learning physics with monotonous learning media makes learning physics boring and requires innovation of learning media that attracts students to support learning activities. The learning media innovation that has been developed is an Android-based learning media created using the Smart Apps Creator software by presenting text, images and videos. This study aims to develop android-based learning media on optical instrument material for high school students and to determine the feasibility of android-based learning media on optical instrument material for high school students and determine student responses to android-based learning media on optical instrument material for high school students. The research method used is Research and Development with the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The results of this study obtained an average expert validation score of 84% by media experts, 76.67% by material experts and 83.33% by linguists. So that obtained an average total of 81.33% with a very good category and suitable for use as a learning media. The response of students to this android-based learning media obtained an average score of 82.23% with a very good category and suitable for use.